PENGARUH KONTEN VIRAL MEDIA SOSIAL TIKTOK “We Listen We Don’t Judge” TERHADAP FENOMENA FOMO PADA GEN Z DI DENPASAR - Anak Agung Sagung Manik Isma Jaya; Ni Made Prasiwi Bestari (Journal of Innovation Research and Knowledge, 2025)
This study aims to analyze the influence of the viral TikTok content "We Listen We Don't Judge" on the Fear of Missing Out (FOMO) phenomenon among Generation Z in Denpasar. The background of this research is based on the phenomenon of the widespread use of TikTok among Gen Z, which has made social media not only a means of entertainment but also an arena for the formation of identity, lifestyle, and social behavior. The "We Listen We Don't Judge" trend creates a space for empathy and openness, but at the same time can trigger social pressure to participate in order to keep up with the flow of digital trends. This study used a qualitative approach with descriptive phenomenology methods, through in-depth interviews, participant observation, and documentation of active Gen Z TikTok users in Denpasar. The results show that Gen Z's involvement in the trend is influenced by the need for cognitive, affective, social, and self-identity gratification, ultimately strengthening the tendency for FOMO. In conclusion, viral TikTok content not only conveys messages of empathy but also acts as a digital socialization agent that shapes Gen Z's social interaction patterns, while also giving rise to a significant FOMO phenomenon